Racoleus, a new genus of sterile filamentous lichen-forming fungi from the tropics, with observations on the nomenclature and typification of Cystocoleus and Racodium - D.L. Hawksworth; R. Santesson; L. Tibell (IMA Fungus)
Raco/eus trichophorus gen. sp. nov. is described for a tropical sterile filamentous lichenized fungus which overgrows various crustose lichens on bark. It shares some features with Cystoco/eus and Racodium, but is unique in having non-lichenized long lateral spines. The genus, which is known from China, the Ivory Coast, and Peru, is of uncertain systematic position; on the basis of morphological similarities, however, it may be referred to "? Capnodia/es (incertae sedis)" ad interim. In addition, the nomenclature and typification of the monotypic genera Cystoco/eus and Racodium are reviewed, and lectotypes selected for the type of each. The available information on the ecology and distribution of these two genera is also summarized, and scanning electron micrographs (SEM) of all three species are presented for the first time.